Trail Runners’ Repeated Participation in Natural Destinations: Insights from Thai Perspectives - Sann, Raksmey; Sang-in, Thanasak; Butt, Phonphirat; Pattajaree, Saharat; Supakichaisin, Podchamarn (Eco-Tourism and Sustainable Development, 2026)
This study explores psychological and social factors influencing participation and repeat behaviour in trail running tourism through the lens of the Theory of Planned Behaviour (TPB). The proposed model combines attitude, subjective norm, perceived behavioural control, motivation, and destination image as predictors of intention, which subsequently affects behaviour and repeat participation. Runner experience is included as a mediating variable between behaviour and repeat participation. Data were gathered from 276 respondents via online and onsite surveys distributed through Thai running communities. Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4.0 was utilised for the analysis. The SEM model demonstrated that the TPB effectively explains trail runners' behavioural intentions and participation in Khon Kaen. However, not all TPB constructs had a significant impact on intention. Of the five predictors, PBC and destination image were significant and positively related, whereas attitude, subjective norms, and motivation were not. Additionally, it was found that intention significantly influences behaviour, which then affects runners’ experiences and their likelihood of returning. Furthermore, runner experience mediates the relationship between behaviour and repeat participation. The findings highlight the importance of destination branding and experiential quality in promoting sustainable sport tourism, providing both theoretical insights and practical implications for event management and regional development.